THE INFLUENCE OF DIGITAL LITERACY ON STUDENTS PROBLEM SOLVING ABILITY IN PHYSICS SUBJECTS - Abimantara, Alexander Yudha; Sinaga, Feliza Paramitha; Perkins, Katherine (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This research aims to measure the effect of digital literacy on students' problem solving abilities in physics subjects which are limited to class XI dynamic fluid material. This research uses quantitative methods with a causal associative research design. The sample for this research was 74 students obtained from the sampling technique, namely purposive sampling. The research instruments used in this study were a questionnaire sheet for the digital literacy variable and a question sheet for the problem solving ability variable. The data analysis technique that will be carried out is inferential statistical analysis using simple linear regression hypothesis testing. The results of this study show a significance value of 0.00, which means it is smaller than 0.05, so there is an influence between digital literacy and students' problem solving abilities. However, this research has limitations, namely it only focuses on measuring the influence and only on dynamic fluid materials.